Patterns of biomechanical demands are associated with musculoskeletal pain in the beginning of professional life: a population-based study - Sara Lourenço; Fábio Araújo; Milton Severo; Luís Cunha Miranda; Filomena Carnide; Raquel Lucas (Nordic Association of Occupational Safety and Health (NOROSH), 2015)
OBJECTIVES: This study aimed to describe patterns of occupational biomechanical demands in the beginning of professional life and to quantify their association with the presence and intensity of regional musculoskeletal pain. METHODS: Cross-sectional data from 21-year-old participants were collected during the third wave of the EPITeen cohort study (N=1733, 37.5% were workers). Ten different work-related biomechanical tasks were characterized. Latent class analysis was conducted to identify empirical patterns of occupational biomechanical demands. The presence and intensity of regional musculoskeletal pain in the previous year were also evaluated. RESULTS: Four patterns of occupational biomechanical demands were found: "low demands", "sitting demands", "repetitive and asymmetric demands", and "high and vibrational demands". When compared to workers with low demands, those with repetitive and asymmetric demands or high and vibrational demands presented 80% higher adjusted odds ratio (OR_adj) of reporting neck/shoulder pain. High and vibrational demands occupations were significantly associated with upper-/lower-back pain in comparison to low demands [OR_adj 1.80, 95% confidence interval (95% CI%) 1.09-2.96]. In addition, workers with sitting demands were more likely to report any or severe upper-/lower-back pain [OR_adj 1.56 (95% CI 0.99-2.45) and 1.66 (95% CI 1.03-2.66), respectively] when compared to those with low demands. CONCLUSIONS: Patterns of high work-related physical demands were associated with the presence of neck/shoulder pain and severity of upper-/lower-back pain. This emphasizes that even short-term biomechanical exposures at the workplace may be involved in the etiology of musculoskeletal complaints.